High-entropy multi-principal-element rare earth aluminate material and preparation method thereof

By employing a high-entropy multi-principal rare-earth aluminate material preparation method, the method utilizes the position and valence differences between rare-earth ions and Al3+ to form a multi-photon scattering interface and synergistic coupling of phonon modes. Combined with rapid high-temperature synthesis using Joule heating equipment, the method solves the problem of insufficient reflectivity and emissivity in existing radiative cooling materials, achieving efficient and stable radiative cooling material preparation suitable for building energy conservation and aerospace thermal control.

CN121202175APending Publication Date: 2025-12-26LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511455310.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-13
Publication Date
2025-12-26

AI Technical Summary

Technical Problem

Existing radiation cooling materials have shortcomings in balancing ultraviolet reflectivity, mid-infrared transparency, and weather resistance. Furthermore, traditional synthesis methods limit the selection of element combinations and synthesis parameters, making it difficult to achieve efficient large-scale applications.

Method used

A high-entropy multi-principal-element rare-earth aluminate material preparation method was adopted. By introducing multiple rare-earth elements in various valence states into the garnet structure, and utilizing the position and valence differences between rare-earth ions and Al3+, multiple photon scattering interfaces and phonon modes were formed and synergistically coupled. Combined with the rapid high-temperature synthesis technology of Joule heating equipment, the material achieved high reflectivity and high emissivity.

Benefits of technology

The material has a reflectivity ≥0.92 in the 0.3~2.5 μm band and an emissivity ≥0.93 in the 8~13 μm band. It has good high-temperature stability and resistance to oxidation and corrosion. It has high synthesis efficiency and low energy consumption, making it suitable for extreme scenarios such as building energy conservation and aerospace thermal control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121202175A_ABST
    Figure CN121202175A_ABST
Patent Text Reader

Abstract

The invention relates to a high-entropy multi-principal-element rare earth aluminate material. The chemical formula of the high-entropy multi-principal-element rare earth aluminate material is (A1 < x > A < 2 > < y > A < 3 > < z > A < 4 > A < 5 > < v >) < 3 > Al < 5 > O < 12 >, a1, A2, A3, A4 and A5 are any five rare earth ions of Y, La, Ce, Gd, Nd, Pr, Sm, Ho, Er, Yb and Lu, and A3, A4 and A5 are any five rare earth ions of Y, La, Ce, Gd, Nd, Pr, Sm, Ho, Er, Yb and Lu. A site in the garnet structure is randomly occupied by five rare earth ions, the rare earth ions are located in the center of a dodecahedron, and the rare earth ions are located in a deformed cube formed by eight oxygen; al < 3 + > is located at the B site of the octahedron and the tetrahedron to form [AlO6-] octahedron and [AlO4-] tetrahedron frameworks. Meanwhile, the invention also discloses a preparation method of the material. The method is simple to operate and high in production efficiency, and the obtained material has both high-reflectivity visible light-near infrared band and atmospheric window, and can be applied to extreme scenes such as building energy conservation and aerospace thermal control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of radiation cooling materials technology, and in particular to a high-entropy multi-principal-element rare-earth aluminate material and its preparation method. Background Technology

[0002] Radiation-induced sky cooling (RSC) is a passive cooling technology based on the long-wave thermal radiation exchange between the Earth's surface and the cosmic background radiation (~4 K). It directly transfers heat to outer space through an atmospheric transparent window (8-13 μm) without mechanical energy consumption, making it an important renewable energy technology for building a low-carbon society. Its core lies in developing radiation-induced cooling materials with high long-wave emissivity and high solar spectrum reflectivity to overcome interference from solar radiation. Currently, RSC has been applied in building envelope cooling, photovoltaic system heat dissipation, and energy-saving air conditioning systems. However, traditional materials (such as metal reflective substrates and polymer-based composites) still face challenges such as ultraviolet degradation, insufficient mechanical strength, and the difficulty in balancing mid-infrared transparency and weather resistance. Furthermore, existing research lacks systematic analysis of the correlation between material performance parameters and environmental factors (such as humidity and temperature fluctuations), hindering its large-scale application.

[0003] Traditional mono / dicomponent aluminates (such as YAlO3 and LaAlO9) are limited by the single Al-O bond vibration mode and low configuration entropy, making it difficult to achieve both thermal emissivity and solar reflectivity, and they are prone to structural degradation under high temperature / corrosive environments.

[0004] Existing HEO synthesis methods mainly rely on prolonged muffle furnace heating, which not only limits high-throughput screening of synthesis parameters and component ratios but also severely restricts the selection of element combinations. Therefore, developing a rapid, controllable, and expandable novel synthesis strategy is of great significance for fully exploiting the compositional advantages of high-entropy materials. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a high-entropy multi-principal-element rare earth aluminate material that has both high reflectivity in the visible-near infrared band and atmospheric window.

[0006] Another technical problem to be solved by the present invention is to provide a method for preparing the high-entropy multi-principal-element rare earth aluminate material.

[0007] To address the aforementioned problems, the present invention provides a high-entropy multi-principal-element rare-earth aluminate material, characterized in that: the chemical formula of the material is (A... 1x A 2y A 3z A 4u A 5v )3Al5O 12The structure forms a garnet structure, where A1, A2, A3, A4, and A5 are any five rare earth ions selected from Y, La, Ce, Gd, Nd, Pr, Sm, Ho, Er, Yb, and Lu, with a metal atom molar ratio of x:y:z:u:v:5, satisfying x+y+z+u+v=1. In the garnet structure, the A-site is randomly occupied by the five rare earth ions, which are located at the center of a dodecahedron and within a deformed cube formed by eight oxygen atoms. Al 3+ Located at the B sites of octahedrons and tetrahedrons, forming [AlO 6- Octahedron and [AlO] 4- Tetrahedral framework.

[0008] The material has a reflectivity ≥0.92 in the 0.3~2.5 μm band and an emissivity ≥0.93 in the 8~13 μm band.

[0009] The preparation method of the high-entropy multi-principal rare earth aluminate material described above is characterized by: the method referring to the use of Y2O3, La2O3, Ce2O3, Gd2O3, Nd2O3, Pr6O 11 Using any five powders selected from Sm2O3, Ho2O3, Er2O3, Yb2O3, and Lu2O3, and Al2O3 powder as raw materials, the mixture is ball-milled according to the metal atomic molar ratio of x:y:z:u:v:5, satisfying x+y+z+u+v=1. After drying and grinding, the mixture powder is obtained. The mixture powder is subjected to high-temperature thermal shock in a Joule heating device, and after cooling and grinding, rare earth aluminate material is obtained.

[0010] The conditions for ball milling and mixing refer to using a planetary ball mill, wet ball milling with anhydrous ethanol as the dispersion medium, a ball milling speed of 300~500 r / min, a ball milling time of 12~24 hours, and a ball-to-ethanol mass ratio of 2~4:1:3.

[0011] The conditions for high-temperature thermal shock are a maximum temperature of 1000~1600 ℃, a heating time of 30~60 ms, and a calcination time of 5~10 minutes.

[0012] The atmosphere for the thermal shock is one of argon, vacuum, and air.

[0013] Compared with the prior art, the present invention has the following advantages: 1. This invention involves incorporating various rare earth elements (such as La) into the A-site of garnet structure. 3+ Ce 3+ / Ce 4+ Pr 3+ / Pr 4+The differences in local charge and ionic radius of rare earth ions with different valence states lead to lattice distortion in the material, forming a multiple photon scattering interface, thereby improving the diffuse reflectance efficiency of the solar spectrum. Furthermore, rare earth elements possess unique electronic configurations and rich energy level structures. Multivalent rare earth ions exhibit a rich distribution of alternating 4f-4f and 4f-5d transition energy levels, which can tune the optical bandgap and effectively improve ultraviolet-visible light (0.3~2.5 μm) reflectance, with a reflectance ≥0.92 in the 0.3~2.5 μm band.

[0014] 2. In this invention, the rare earth ions are located at the A-site of the dodecahedron, Al 3+ Located in [AlO 6- Octahedron and [AlO] 4- The B-site of the tetrahedron is used to enhance infrared radiation through phonon mode cooperative coupling and defect engineering, and multivalent A-site ions are used in conjunction with AlO2. 6- The bond length / bond angle differences of the octahedron induce local lattice vibrations, which enhance its emissivity in the atmospheric window band (8~13 μm). At the same time, the coexistence of multiple valence states forms controllable anion / cation defects through charge compensation mechanisms, which enhances the local resonance of mid-infrared photons and further optimizes the intensity and bandwidth of the thermal emission peak, resulting in a solar absorptivity of ≥0.93 in the 8~13 μm band.

[0015] 3. This invention, through dual-site high-entropy component regulation at both the A and B sites, introduces significant lattice distortion into the unit cell, forming a multi-level synergistic effect dominated by high configurational entropy—namely, mass disorder, ion size disorder, and charge disorder. This helps reduce the Gibbs free energy, thereby enabling the material to exhibit entropy-driven structural stability, possessing excellent high-temperature stability and resistance to oxidation and corrosion. Simultaneously, the doping of numerous components into a single-phase solid solution structure provides ample space for optimizing material properties.

[0016] 4. The preparation method of this invention uses a Joule heating device, which has high temperature capability (>3000 ℃) and rapid heating and cooling rate (>10 ℃). 2 This method, characterized by its rapid heating and cooling speed (℃ / s), short duration (milliseconds to seconds), and high energy efficiency (approximately 100%), achieves rapid heating and cooling of materials through instantaneous high current, avoiding phase separation or grain coarsening caused by prolonged annealing. This enables the efficient synthesis of single-phase high-entropy oxides in a short time. Furthermore, this method exhibits an extremely high growth rate, five orders of magnitude faster than traditional heating-based methods; simultaneously, the energy cost is reduced to 9.55 × 10⁻⁶. -6 Kilowatt-hours per square centimeter, which is six orders of magnitude lower than the traditional method.

[0017] 5. This invention is simple to operate, has high production efficiency, requires no complicated post-processing, and can be industrialized. The resulting materials can be applied to extreme scenarios such as building energy conservation and aerospace thermal control. Attached Figure Description

[0018] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.

[0019] Figure 1 This is Example 1 (Y) of the present invention. 0.2 La 0.2 Ce 0.2 Gd 0.2 Nd 0.2 )3(Al)5O 12 XRD pattern.

[0020] Figure 2 This is Example 1 (Y) of the present invention. 0.2 La 0.2 Ce 0.2 Gd 0.2 Nd 0.2 )3(Al)5O 12 Spectra in the 0.3–2.5 μm and 8–13 μm bands.

[0021] Figure 3 This is Example 1 (Y) of the present invention. 0.2 La 0.2 Ce 0.2 Gd 0.2 Nd 0.2 )3(Al)5O 12 Spectra in the 0.3–2.5 μm and 8–13 μm bands after thermal stability experiments.

[0022] Figure 4 This is Example 1 (Y) of the present invention. 0.2 La 0.2 Ce 0.2 Gd 0.2 Nd 0.2 )3(Al)5O 12 SEM images before and after corrosion. Detailed Implementation

[0023] A high-entropy multi-principal-element rare-earth aluminate material, the chemical formula of which is (A 1x A 2y A 3z A 4u A 5v )3Al5O 12The structure forms a garnet structure, where A1, A2, A3, A4, and A5 are any five rare earth ions selected from Y, La, Ce, Gd, Nd, Pr, Sm, Ho, Er, Yb, and Lu, with a metal atom molar ratio of x:y:z:u:v:5, satisfying x+y+z+u+v=1. In the garnet structure, the A-site is randomly occupied by the five rare earth ions, which are located at the center of a dodecahedron and within a deformed cube formed by eight oxygen atoms (D2 symmetry). Al 3+ Located at the B sites of octahedrons and tetrahedrons, forming [AlO 6- Octahedron and [AlO] 4- Tetrahedral framework.

[0024] The material has a reflectivity ≥0.92 in the 0.3~2.5 μm band and an emissivity ≥0.93 in the 8~13 μm band.

[0025] A method for preparing high-entropy multi-principal rare-earth aluminate materials, wherein the method refers to using Y2O3, La2O3, Ce2O3, Gd2O3, Nd2O3, Pr6O 11 Using any five powders selected from Sm₂O₃, Ho₂O₃, Er₂O₃, Yb₂O₃, and Lu₂O₃, along with Al₂O₃ powder, as raw materials, a planetary ball mill was used. Anhydrous ethanol was used as the dispersion medium, and the mixture was wet-milled according to a metal atomic molar ratio of x:y:z:u:v:5, satisfying x+y+z+u+v=1. The milling speed was 300-500 r / min, and the milling time was 12-24 hours. The mass ratio (g / g) of the ball-to-material mixture to anhydrous ethanol was 2-4:1:3. After mixing, the mixture was dried to constant weight at 80-100 °C and then ground to obtain the powdered mixture. The powdered mixture was then subjected to high-temperature thermal shock in a Joule heating apparatus under one of the following atmospheres: argon, vacuum, or air. The maximum temperature was 1000-1600 °C, the heating time was 30-60 ms, and the calcination time was maintained for 5-10 minutes. Finally, after cooling at room temperature and grinding, high-entropy multi-principal-element rare-earth aluminate material is obtained.

[0026] Example 1: A method for preparing a high-entropy multi-principal-element rare-earth aluminate material: Y₂O₃ (1.5 mol), La₂O₃ (1.5 mol), Ce₂O₃ (1.5 mol), Gd₂O₃ (1.5 mol), Nd₂O₃ (1.5 mol), and Al₂O₃ (2.5 mol) powders were weighed out according to a metal atomic molar ratio of 3:3:3:3:3:5 as raw materials. Zirconia balls, raw materials, and anhydrous ethanol were added to a planetary ball mill at a ball mill mass ratio (g / g) of 2:1:3. The milling was performed for 1 hour at 300 r / min, followed by a 10-min pause, constituting one milling cycle. This was repeated for another hour at 300 r / min, for a total of 24 hours. The mixture was dried at 80–100 °C after milling, and then ground to obtain the final powder. The powder was then subjected to high-temperature thermal shock in a Joule heating device, with a maximum temperature of 1000 °C, a heating time of 30 ms, and a calcination time of 8 minutes. Argon gas was used in the calcination atmosphere, and the product was finally ground to obtain a single-phase (Y) gas. 0.2 La 0.2 Ce 0.2 Gd 0.2 Nd 0.2 )3(Al)5O 12 Rare earth aluminate materials.

[0027] Figure 1 For (Y) 0.2 La 0.2 Ce 0.2 Gd 0.2 Nd 0.2 )3(Al)5O 12 The XRD pattern of the rare earth aluminate material shows that the spectral lines are in excellent agreement with the spectral lines with garnet structure (PDF#09-0310) in the ICDD database, indicating that the prepared rare earth aluminate material has a garnet structure.

[0028] Regarding the obtained (Y) 0.2 La 0.2 Ce 0.2 Gd 0.2 Nd 0.2 )3(Al)5O 12 Radiation performance evaluation of rare earth aluminate materials: Test method: The reflectance performance of the material was evaluated using a Lambda 950 UV / Vis / NIR spectrophotometer (equipped with a 150 mm integrating sphere) manufactured by PerkinElmer, USA. The reflectance spectrum in the 0.3~2.5 μm band was measured, and the solar reflectance was calculated according to the calculation formula in the international standard ISO 9845-1 (1992).

[0029] The emissivity of the sample in the 8-13 μm band was tested using the Japanese TSS-5X infrared radiation meter.

[0030] The amount of test sample used was 0.2 g.

[0031] like Figure 2 As shown, the reflectivity of this rare earth aluminate material is 0.95 in the 0.3~2.5 μm band and the emissivity is 0.96 in the 8~13 μm band.

[0032] The prepared aluminate material was placed in an air atmosphere in a box furnace and subjected to a 24-hour thermal stability test at 900 °C. Figure 3 As shown, after thermal stability testing, the reflectivity of this rare earth aluminate material is 0.943 in the 0.3~2.5 μm band and the emissivity is 0.951 in the 8~13 μm band.

[0033] The prepared aluminate material was subjected to corrosion resistance tests under NaCl / Na2SO4 (1:1) conditions at 700℃ for 40 hours. Figure 4 As shown, the surface of the rare earth aluminate material remains intact after 40 hours of corrosion, without any corrosion pits.

[0034] Example 2: A method for preparing a high-entropy multi-principal-element rare-earth aluminate material: Y₂O₃ (1.5 mol), La₂O₃ (1.5 mol), Ce₂O₃ (1.5 mol), Pr₂O₃ (1.5 mol), Sm₂O₃ (1.5 mol), and Al₂O₃ (2.5 mol) powders were weighed out according to a metal atomic molar ratio of 3:3:3:3:3:5 as raw materials. Zirconia balls, raw materials, and anhydrous ethanol were added to a planetary ball mill at a ball mill mass ratio (g / g) of 3:1:3. The milling was performed for 1 hour at 300 r / min, followed by a 10-min pause, constituting one milling cycle. This was repeated for another hour at 300 r / min, for a total of 24 hours. The mixture was dried at 80–100 °C after milling, and then ground to obtain the final powder. The powder was then subjected to high-temperature thermal shock in a Joule heating device, with a maximum temperature of 1400 °C, a heating time of 40 ms, and a calcination time of 5 minutes. The calcination atmosphere is air, and the final product is obtained by grinding, yielding a single-phase (Y) solution. 0.2 La 0.2 Ce 0.2 Pr 0.2 Sm 0.2 )3(Al)5O 12 Rare earth aluminate materials.

[0035] Regarding the obtained (Y) 0.2 La 0.2Ce 0.2 Pr 0.2 Sm 0.2 )3(Al)5O 12 The radiation performance and thermal stability of rare earth aluminate materials were evaluated. The test methods and sample amounts were the same as in Example 1.

[0036] The results showed that the reflectivity of this rare earth aluminate material was 0.945 in the 0.3–2.5 μm wavelength range and 0.95 in the 8–13 μm wavelength range. After thermal stability testing, the reflectivity of this rare earth aluminate material was 0.938 in the 0.3–2.5 μm wavelength range and 0.946 in the 8–13 μm wavelength range.

[0037] Example 3: A method for preparing a high-entropy multi-principal-element rare-earth aluminate material: Y₂O₃ (1.5 mol), La₂O₃ (1.5 mol), Ce₂O₃ (1.5 mol), Ho₂O₃ (1.5 mol), Er₂O₃ (1.5 mol), and Al₂O₃ (2.5 mol) powders were weighed out according to a metal atomic molar ratio of 3:3:3:3:3:5 as raw materials. Zirconia balls, raw materials, and anhydrous ethanol were added to a planetary ball mill at a ball mill mass ratio (g / g) of 4:1:3. The milling was performed for 1 hour at 500 r / min, followed by a 10-min pause, constituting one milling cycle. This was repeated for another hour at 500 r / min, for a total of 10 hours of milling. The mixture was dried at 80–100 °C after milling, and then ground to obtain the final powder. The powder was then subjected to high-temperature thermal shock in a Joule heating device, with a maximum temperature of 1500 °C, a heating time of 50 ms, and a calcination time of 6 minutes. The calcination atmosphere is air, and the final product is obtained by grinding, yielding a single-phase (Y) solution. 0.2 La 0.2 Ce 0.2 Ho 0.2 Er 0.2 )3(Al)5O 12 Rare earth aluminate materials.

[0038] Regarding the obtained (Y) 0.2 La 0.2 Ce 0.2 Ho 0.2 Er 0.2 )3(Al)5O 12 The radiation performance and thermal stability of rare earth aluminate materials were evaluated. The test methods and sample amounts were the same as in Example 1.

[0039] The results showed that the reflectivity of this rare earth aluminate material was 0.94 in the 0.3–2.5 μm wavelength range and 0.947 in the 8–13 μm wavelength range. After thermal stability testing, the reflectivity of this rare earth aluminate material was 0.934 in the 0.3–2.5 μm wavelength range and 0.944 in the 8–13 μm wavelength range.

[0040] Example 4: A method for preparing a high-entropy multi-principal-element rare-earth aluminate material: Y₂O₃ (1.5 mol), La₂O₃ (1.5 mol), Ce₂O₃ (1.5 mol), Yb₂O₃ (1.5 mol), Lu₂O₃ (1.5 mol), and Al₂O₃ (2.5 mol) powders were weighed out according to a metal atomic molar ratio of 3:3:3:3:3:5 as raw materials. Zirconia balls, raw materials, and anhydrous ethanol were added to a planetary ball mill at a ball mill mass ratio (g / g) of 3:1:3. The milling was performed for 1 hour at 400 r / min, followed by a 10-min pause, constituting one milling cycle. This was repeated for another hour at 400 r / min, for a total of 12 hours. The mixture was dried at 80–100 °C after milling, and then ground to obtain the final powder. The powder was then subjected to high-temperature thermal shock in a Joule heating device, with a maximum temperature of 1500 °C, a heating time of 60 ms, and a calcination time of 10 minutes. The calcination atmosphere is under vacuum, and after grinding, a single-phase (Y) is obtained. 0.2 La 0.2 Ce 0.2 Yb 0.2 Lu 0.2 )3(Al)5O 12 Rare earth aluminate materials.

[0041] Regarding the obtained (Y) 0.2 La 0.2 Ce 0.2 Yb 0.2 Lu 0.2 )3(Al)5O 12 The radiation performance and thermal stability of rare earth aluminate materials were evaluated. The test methods and sample amounts were the same as in Example 1.

[0042] The results showed that the reflectivity of this rare earth aluminate material was 0.92 in the 0.3–2.5 μm wavelength range and 0.93 in the 8–13 μm wavelength range. After thermal stability testing, the reflectivity of this rare earth aluminate material was 0.918 in the 0.3–2.5 μm wavelength range and 0.926 in the 8–13 μm wavelength range.

[0043] The above description only illustrates the preferred embodiments of the present invention and should not be construed as limiting the scope of the claims. The present invention is not limited to the above embodiments, and variations in its specific structure are permitted. All modifications made within the scope of the independent claims of this invention are also within the scope of protection of this invention.

Claims

1. A high-entropy multi-principal-element rare-earth-aluminate material, characterized in that: The chemical formula of the material is (A 1x A 2y A 3z A 4u A 5v )3Al5O 12 ; form a garnet structure, wherein: A1, A2, A3, A4, A5 are any five kinds of rare earth ions in Y, La, Ce, Gd, Nd, Pr, Sm, Ho, Er, Yb, Lu, the molar ratio of metal atoms is x:y:z:u:v:5, and x+y+z+u+v=1; the A site in the garnet structure is randomly occupied by the five kinds of rare earth ions, the rare earth ions are in the center of the dodecahedron, and the rare earth ions are in the distorted cube formed by eight oxygens; Al 3+ In the B site of octahedron and tetrahedron, [AlO 6- ] octahedron and [AlO 4- ] tetrahedron framework are formed.

2. The high-entropy multi-principal element rare-earth aluminate material of claim 1, wherein: The reflectivity of the material is greater than or equal to 0.92 in the 0.3-2.5 mu m wave band, and the emissivity is greater than or equal to 0.93 in the 8-13 mu m wave band.

3. The preparation method of the high-entropy multi-main-element rare earth aluminates material according to claim 1 or 2, characterized in that: The method is to use any five kinds of powders selected from Y2O3, La2O3, Ce2O3, Gd2O3, Nd2O3, Pr6O 11 , Sm2O3, Ho2O3, Er2O3, Yb2O3 and Lu2O3 and Al2O3 powder as raw materials, ball-mill mix according to the molar ratio of metal atoms x:y:z:u:v:5, and x+y+z+u+v=1, dry, grind to obtain the mixture powder; the mixture powder is subjected to high-temperature thermal shock in a joule heat device, cooled and ground to obtain the rare earth aluminate material.

4. The preparation method of a high-entropy multi-principal-element rare-earth aluminate material as described in claim 3, characterized in that: The ball-milling mixing condition is that a planetary ball mill is used for wet ball milling with anhydrous ethanol as a dispersion medium, the ball-milling speed is 300-500 r / min, the ball-milling time is 12-24 hours, and the mass ratio of ball, anhydrous ethanol and ball is 2-4:1:

3.

5. The method for preparing a high-entropy multi-principal-element rare-earth aluminate material as described in claim 3, characterized in that: The high-temperature thermal shock condition is that the maximum temperature is 1000-1600 DEG C, the temperature rising time is 30-60 ms, and the calcination time is kept for 5-10 minutes.

6. The method for preparing a high-entropy multi-principal-element rare-earth aluminate material as described in claim 3, characterized in that: The thermal shock atmosphere is one of argon, vacuum and air.